2014
DOI: 10.1002/mc.22220
|View full text |Cite
|
Sign up to set email alerts
|

Asiatic acid induces endoplasmic reticulum stress and apoptotic death in glioblastoma multiforme cells both in vitro and in vivo

Abstract: Glioblastoma multiforme (GBM) is an untreatable malignancy. Existing therapeutic options are insufficient, and adversely affect functional and non-cancerous cells in the brain impairing different functions of the body. Therefore, there is an urgent need for additional preventive and therapeutic non-toxic drugs against GBM. Asiatic acid (AsA; 2,3,23-trihydroxy-12-ursen-28-oic acid, C30H48O5) is a natural small molecule widely used to treat various neurological disorders, and the present research investigates As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 42 publications
0
36
0
Order By: Relevance
“…In recent studies, molecular targets involved in apoptotic processes have created an opportunity to develop more effective drugs for cancer. In this regard, UPR-signaling pathway is an interesting area of investigations (6,9,16). Although relationships of Bv and different cellular apoptotic pathways have been described, UPR activation has been uncovered as an important mechanism of Bv impact on various tumor cell lines (13).…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, molecular targets involved in apoptotic processes have created an opportunity to develop more effective drugs for cancer. In this regard, UPR-signaling pathway is an interesting area of investigations (6,9,16). Although relationships of Bv and different cellular apoptotic pathways have been described, UPR activation has been uncovered as an important mechanism of Bv impact on various tumor cell lines (13).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have demonstrated the pro-apoptotic and cell growth inhibitory activity of AA in the liver, breast, skin, brain, and gastrointestinal tumor cells (Lee et al, 2002 ; Hsu et al, 2005 ; Park et al, 2005 ; Cho et al, 2006 ; Tang et al, 2009 ; Kavitha et al, 2015 ; Wu et al, 2015 ). AA treatment was found to attenuate inflammation, tumor cell proliferation, and induce mitochondrial pathway of apoptosis.…”
Section: Asiatic Acid In Cancermentioning
confidence: 99%
“…Natural products are emerging as an important source of new potential candidates for the treatment or as adjuvant therapy for glioblastoma (41)(42)(43)(44). In GBM, natural triterpenes were shown to induce cell arrest and/or apoptosis both in vitro (45,46) and in vivo (47), to inhibit migration and invasion (48) and to attenuate TMz resistance (49). Results presented in this study show that the pentacyclic triterpene pomolic acid (PA) is cytotoxic to GBM cell lines and that this effect is associated with induction of apoptosis, uncoupling of mitochondria potential, increase in ROS production and modulation of MDR pump, MRP1/ABCC1 activity.…”
Section: Malignant Central Nervous System Neoplasms Particularlymentioning
confidence: 99%